2008
DOI: 10.1007/s11218-008-9055-1
|View full text |Cite
|
Sign up to set email alerts
|

First impressions and professor reputation: influence on student evaluations of instruction

Abstract: We examined the effects of professor reputation versus first impressions on student evaluations of instruction. Students in 19 Psychology courses completed course evaluation surveys either before meeting the instructor or 2 weeks into the semester. Both groups then completed the course evaluation again at the end of the semester. Unlike evaluations completed prior to meeting the professor, students' ratings 2 weeks into the semester did not differ from end-of-semester evaluations. Therefore, students considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Research on thin-slice judgments has shown that initial impressions of instructors may be just as reliable as impressions informed by more experience and time. Furthermore, related research suggests that these first impressions may be weighted more heavily than other sources of information (e.g., instructor reputation; see Buchert et al 2008). It is thus likely that participants in this study provided judgments that were as reliable as students with a vested interest in the course.…”
Section: Limitations and Future Directionsmentioning
confidence: 83%
“…Research on thin-slice judgments has shown that initial impressions of instructors may be just as reliable as impressions informed by more experience and time. Furthermore, related research suggests that these first impressions may be weighted more heavily than other sources of information (e.g., instructor reputation; see Buchert et al 2008). It is thus likely that participants in this study provided judgments that were as reliable as students with a vested interest in the course.…”
Section: Limitations and Future Directionsmentioning
confidence: 83%
“…Moreover, the cognitive consistency perspective provides a framework in which prior central trait research conducted in an educational setting can be integrated. For example, in the Babad et al (1999) and Buchert et al (2008) studies, students were exposed to their professor throughout the semester and initial attitudes form about the professor changed. In contrast, in the Griffin (2001) andMcClleland (1970) studies, students were given a prompt to recall their initial attitudes about their professors.…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed a questionnaire modeled after Buchert et al (2008) which included items similar to those found on a university-sponsored teacher evaluation form. The following items measured perceived instructor approachability: "The instructor encourages students to ask questions and express their knowledge".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dado el carácter transversal de los estudios analizados, proponemos como investigaciones futuras la realización de estudios longitudinales para determinar la perdurabilidad de la credibilidad de los docentes, es decir, analizar si la percepción del estudiante sobre la credibilidad del profesor se mantiene o cambia a lo largo del curso académico y determinar qué variables contribuyen al mantenimiento o alteración de dichas percepciones. Al respecto, existen ciertas investigaciones acerca de la perdurabilidad de las percepciones de los estudiantes sobre los profesores aunque con conclusiones distintas ya que algunos estudios señalan que las percepciones iniciales se mantienen hasta el final del año académico mientras que otros destacan que cambian conforme avanza el curso (Babad, Kaplowitz y Darley, 1999;Buchert, Laws, Apperson y Bregman, 2008;Clayson, 2013).…”
Section: Discusión Y Conclusionesunclassified